Postoperative delirium and factors related in a cardiac surgery unit care - Julia de las Pozas Abril (Fundación para el Desarrollo de la Enfermería, 2011)
Objective: Describe the incidence of postoperative delirium and related risk factors associated with this complication in patients undergoing cardiac surgery. Method: Cohort study conducted for 3 months in a sample of 105 patients undergoing cardiac surgery in a hospital in Madrid. The emergence of delirium with scale ICDSC (Intensive Care Delirium Screening Checklist) was measured during the first five days of postoperative and collected data on preoperative, intra-operative and post-operative factors to relate to the emergence of delirium. Results: 95 Patients studied, 15 of them developed delirium, which means an incidence of 15.7%. We found that there was a significant relationship between delirium appearance and age of the patients, the presence of atrial fibrillation, intubation orotraqueal time and the administration of adrenaline during the immediate post-operative management. The multivariable model showed the duration of orotraqueal intubation to be independently associated with delirium. Conclusions: The incidence of delirium found in this study as well as the identification of the time of orotraqueal intubation as independent risk factor supposes a new contribution to the knowledge of this postoperative complication and allow us to begin to evaluate its importance in the unit of cardiac surgery.